Efektivitas Pelaksanaan Pendidikan Sosial dan Finansial melalui Home Education Play di PAUD Inklusif - Fatimah Zahro, Ifat; Dwi Tresna Santana, Fifiet; Robiyyah, Robiyyah (ACIECE, 2019)
This study aims to determine the effectiveness of the implementation of social and financialeducation through Home Education Play in inclusive PAUD. Home Education Play (HEP) is a form of involving parents at home with play activities to improve the character of sharing, saving, saving and responsibility. This research was conducted using a qualitative approach, and was conducted at the PAUD Melati 06 Cimahi Post which is an PAUD that organizes inclusive education. The results of the study are as follows: (1) The existence of parents / family involvement in the implementation of social and financial education in PAUD Melati 06 Post; (2) Applying the Home Education Play method, effective to improve the ability of social education and financial early childhood